(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
Many factors associated with river flow are vague, subjective and difficult to quantify. The fuzzy logic method is very useful for a problem solving approach such as small hydropower. The rule base and membership functions have a great impact on the performance and efficiency of the power plant, as well as on the optimization of the production of small hydro power plants in the high mountain region, especially in Uzbekistan. The performance of a fuzzy linguistic variable can be easily characterized in general terms. The paper initially presents a new Fuzzy Logic Controller (FCL) method for the safe control of dam reservoirs through weir gates.